Empirical Investigation Of Walking Speed For Bi-Directional Flow At Angled-Walkway - Mohamed Izham, Aimi Syuhada (Universiti Sains Malaysia, 2018)
Pedestrian walking speed is influenced by the following factors such as density of pedestrian, width of walkway, and angle of walkway. There are many research studies that have been done to analyse the pedestrian dynamics on unidirectional pedestrian flows on angled-walkway. However, the study on the movement of crowds on bi-directional flow at the angled-walkway is relatively rare. Therefore, this study is conducted to determine empirically walking speed of pedestrian for bidirectional free flows at angled-walkway. For this experiment, 60 participants are assigned to perform various tasks in walking at straight walkway, as the velocity was used as a baseline to in this experiment before the pedestrians were asked to traverse along different widths(1.5m, 2.25m and3m) of 90°angled-walkway. The videos have been captured using GoPro Camera mounted on the ceiling at Dewan Serbaguna, Univeristi Sains Malaysia,Engineering Campus which then the velocity of pedestrians was determined by tracking their trajectories. The result includes the walking speed by gender, and the effect of the corner on the behaviour of the pedestrians and their approaching speeds. It was found that that average walking speed of female, is higher than average walking speed of male. It was observed that pedestrian tend to walk closer to the inner corner and the pedestrian to reduce their speed when approaching the corner. The results are of particular importance for designing the structure especially walking at walkway and also beneficial for the design of an emergency response plan.